Brief Report: HIV Testing, Diagnosis of HIV Infection, Linkage to Medical Care, and Interview for Partner Services Among Transgender Persons—United States, 2012–2017. (15th April 2021) - Mulatu, Mesfin S.; Wang, Guoshen; Song, Wei; Keatley, JoAnne; Kudon, Hui Zhang; Wan, Choi; Rao, Shubha
Abstract : Background: Transgender persons are at high risk for HIV infection. Testing is a key component of the national effort to end the HIV epidemic in the United States. Setting: Sixty-one local and state health departments and 150 community-based organizations funded by the Centers for Disease Control and Prevention to conduct HIV testing programs. Methods: We analyzed HIV testing data submitted to the Centers for Disease Control and Prevention by funded health departments and community-based organizations during 2012–2017. Descriptive analysis examined patterns of HIV testing and key outcomes (diagnosis of HIV infection, linkage to HIV medical care, and interview for partner services) among transgender persons. Multivariate robust Poisson regression was used to assess associations between HIV testing outcomes and demographic characteristics, census region, and test setting. Results: A total of 82, 818 HIV tests were provided to transgender persons. Of these, 2280 (2.8%) transgender persons were diagnosed with HIV infection; 1556 (1.9%) received a new and 724 (0.9%) a previous diagnosis with HIV infection. The highest percentage of new HIV diagnosis was found among persons tested in correctional settings (4.6%), non-Hispanic Blacks (3.5%) and transgender women (2.4%). Among newly diagnosed persons, 85.0% were linked to HIV medical care ⩽90 days after diagnosis and 63.5% were interviewed for partner services. Conclusions: HIV positivity was high, and the delivery of partner services was low, among transgender persons. HIV testing outcomes among transgender persons varied significantly by demographic characteristics and test setting. HIV prevention programs that are responsive to the needs of transgender persons may address gender-related disparities in HIV testing outcomes.